The Role of Laparoscopy in Management of Congenital Anomalies of the Müllerian System: Literature Review and Case Series - Ettedal A. Aljahdali, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Structural defects of the female reproductive tract become apparent at varying chronologic times during intrauterine life. The diagnosis of all female reproductive tract abnormalities has benefited from enhancements in imaging techniques and the surgical treatment thereof has improved due to advances in the techniques and instrumentation of both surgical and non-surgical procedures. In the last decade, laparoscopy has become increasingly popular and has successfully replaced several open surgical procedures. It has been applied to many aspects of gynecological surgery and has become the procedure of choice for gynecological surgery. A review of the recent literature continues to support the utilization of laparoscopy for the management of genital tract malformation. This review aims to appraise the recent literature to determine how laparoscopy may aid in the diagnosis of reproductive tract anomalies and their treatment, its success in replacing the open surgery in some cases, and the presentation of some cases that were successfully diagnosed and treated with laparoscopy.